Despotism and excessive control and their impact on isolation in the Fatimid era (358-567 AH / 969-1171 AD) - Israa Abd alridha Haddab; Ammar Mardi Allawi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The Fatimid state in Egypt (358-567 AH / 969-1171 AD) lasted for two centuries and had a name on the scene of historical events ?She followed many policies and regulations to lead and control the affairs of the state?Among these policies was dismissal and job exclusion ?This policy was used by the Fatimid State as part of its internal and external governance. Some officials of the Fatimid State, despite their stature, began to tyrannize their legitimate duties and to act .This prompted the Fatimid caliphs to use the Isolation policy as an administrative measure to curb their tyranny and eliminate their tyranny?both on the country's population and on the Fatimid Caliphate itself.